Autonomy-connectedness in collectivistic cultures: An exploratory cross-cultural study among Portuguese natives, Cape-Verdean and Chinese people residing in Portugal. (January 2017) - Moleiro, Carla; Ratinho, Inês; Bernardes, Sonia
Abstract: The present investigation focuses on a recent personality trait construct, Autonomy-connectedness. This concept has been proposed as a three-dimensional variable (self-awareness, sensitivity to others, and capacity to manage new situations), which intends to reflect a more gender- and culture- sensitive notion of autonomy rather than a value based on individualism and hegemonic masculinity. Two studies were conducted. Study I (N = 185) aimed to adapt the Autonomy-Connectedness Scale (ACS-30) to Portuguese and evaluate its three dimensions among a Portuguese sample. The subscales showed satisfactory reliability and overall results converge with previous studies on Autonomy-connectedness. Study II aimed to analyze and compare three different cultural groups, namely Portuguese natives and, Chinese and Cape Verdean immigrants residing in Portugal. A total of 90 participants (30 participants per nationality/cultural group) collaborated in the study. The findings suggest cultural differences in autonomy-connectedness, as well as a possible association between acculturation processes and autonomy-connectedness. This study extends to the support of autonomy-connectedness as a conceptually meaningful construct, with contributions to both gender and cross-cultural studies. Highlights: The study extends support to autonomy-connectedness as a conceptually meaningful construct. Autonomy-connectedness presents a gender differentiated focus. Findings suggest a possible link between autonomy-connectedness and acculturation processes.